Climate Change Awareness and Mental Health Impacts among Community College Students in Kathmandu - Adhikari, Laxmi; Timalsina, Umesh; Kafle, Rameshwor (Janajyoti Journal, 2025)
Growing climate change impact on mental health of human beings is a serious public health problem witnessing everywhere of the universe. The study on mental health of young people is critical for knowledge generation process. The overall objective of the study is to examine awareness of climate change and its impact on reported anxiety among community college students of Kathmandu. Cross-sectional explanatory research design is employed with collecting information from 335 graduate students. Univariate, bi-variate and multivariate analysis was performed. The study revealed that about 23 percent of students who learned about climate change from sources other than school, college, or media have reported anxiety symptoms. Multiple regression analysis shows that climate change awareness and anxiety, students who consider climate change a less significant issue are about 11 times more likely to have anxiety symptoms [OR=11.4 (5.1-17.9)] than those who view it as very important in their lives. The study concludes that climate change awareness are critical factor for the self- reported anxiety symptoms of students of community college. While controlling the social factors, the climate change awareness are most influencing factors for anxiety prevalence. This suggests that climatic factors need to be through appropriate strategic approach.